Tipifarnib in recurrent, metastatic HRAS‐mutant salivary gland cancer. Issue 17 (18th June 2020) - Hanna, Glenn J.; Guenette, Jeffrey P.; Chau, Nicole G.; Sayehli, Cyrus M.; Wilhelm, Christian; Metcalf, Robert; Wong, Deborah J.; Brose, Marcia; Razaq, Mohammad; Pérez‐Ruiz, Elisabeth; Cohen, Ezra E. W.; Aggarwal, Rahul; et al.
Abstract : Background: To the authors' knowledge, there are no approved therapies for recurrent, metastatic (R/M) salivary gland carcinoma (SGC), but molecularly targeted therapies warrant ongoing investigation. In the current study, the authors have reported on the efficacy of tipifarnib in patients with aggressive HRAS ‐mutant, R/M SGC. Methods: The current prospective, nonrandomized, multicenter, international cohort study involved 8 centers and was conducted from May 2015 to June 2019. The median follow‐up was 22 months (range, 6‐55 months). Subjects with HRAS ‐mutant R/M SGC (any histology) and disease progression within the last 6 months were enrolled. Tipifarnib was dosed orally twice daily. The authors determined the objective response rate using Response Evaluation Criteria in Solid Tumors (version 1.1), duration of response, and molecular predictors of response. Results: A total of 13 patients with R/M SGC were enrolled; all had received prior systemic therapy (1‐3 regimens). One objective response was observed; an additional 7 of 12 evaluable patients (58%) had stable disease as their best response with a median duration of 9 months (range, 3‐14 months). Five of 7 patients had >10% tumor regression and 6 of 7 had stable disease lasting >6 months. Q61R was the most frequent activating HRAS mutation noted (7 of 13 patients; 54%), but gene variant and allele frequency did not correlate with outcomes. The median progression‐free survival was 7 months (95% confidence interval, 5.9‐10.1 months), and the median overall survival was 18 months (95% confidence interval, 9.6‐22.4 months) with approximately 58.6% of patients alive at 1 year. Survival was similar regardless of HRAS mutant variant or co‐occurring PIK3CA alterations. No participant discontinued treatment because of toxicity. Conclusions: Tipifarnib resulted in modest clinical activity with a promising disease control rate among patients with HRAS ‐mutant, R/M SGC who developed disease progression within the last 6 months. Abstract : In this prospective, multicenter cohort study that includes 13 adults, 1 patient (8%) is found to achieve a partial response to therapy, and an additional 58% of patients demonstrate stable disease (the majority with >10% tumor regression), with responses often found to last >6 months. Tipifarnib demonstrates a meaningful and often durable disease control rate among patients with a more aggressive subgroup of HRAS‐mutant salivary gland cancers, with evidence of a potential benefit across several variant HRAS mutational genotypes and allele frequencies.